Role and Function of KPC and MBL Enzymes in Increasing the Pathogenicity of Pseudomonas Aeruginosa Isolated from Burn Wounds - H Tahmasebi (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Pseudomonas aeruginosa is one of the main causes of hospital infections. Pathogenic factors in this bacterium may play a role in the resistance to carbapenem and beta-lactam. The purpose of this study was to evaluate the role and function of KPC and MBL enzymes in increasing the pathogenicity of Pseudomonas aeruginosa isolated from burn wounds. METHODS: In this cross-sectional study, 63 isolates of Pseudomonas aeruginosa from burn wounds of different patients were isolated using biochemical tests such as fermentation of sugars in the OF medium, oxidase test, and so on. Determination of resistance pattern and strains with metallobetalactamase and carbapenema was done by disc diffusion method. The oprD gene was used for molecular confirmation of isolates. PCR method was used to detect pathogenicity genes. FINDINGS: Out of 63 isolates of Pseudomonas aeruginosa isolated from burn patients, 10 isolates (15.83%) had KPC enzyme and 13 isolates (20.63%) had MBL enzymes. Doripenem, Ertapenem and meropenem were the most frequent. Also, the lasB gene was observed in 43 isolates (68.25%), plcN gene in 41 isolates (65.07%), lasA gene in 20 isolates (31.74%), apr in 60 isolates (95.23%), phzI gene in 53 isolates (84.12%), the phzII gene in 38 isolates (60.31%), phzH gene in 30 isolates (47.61%) and plcH gene in 56 isolates (88.88%). CONCLUSION: The results of this study showed that the production of Carbapnemase and MBL enzymes increased the pathogenicity of Pseudomonas aeruginosa isolated from burn wounds.